Problems and Solutions. Issue 10 (26th November 2022) - Ullman, Daniel H.; Velleman, Daniel J.; Wagon, Stan; West, Douglas B.; ,
Abstract : Proposed problems, solutions, and classics should be submitted online at americanmathematicalmonthly.submittable.com/submit . Proposed problems must not be under consideration concurrently at any other journal, nor should they be posted to the internet before the deadline date for solutions. Proposed solutions to the problems below must be submitted by April 30, 2023. Proposed classics should include the problem statement, solution, and references. More detailed instructions are available online. An asterisk (*) after the number of a problem or a part of a problem indicates that no solution is currently available.